PENDAMPINGAN TEKNIS KONSTRUKSI SEBAGAI UPAYA PENINGKATAN KEBERLANJUTAN INFRASTRUKTUR JALAN LINGKUNGAN DI KELURAHAN WANGON - Sihtasari Devi; Endah Atika (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Environmental roads are essential infrastructure that supports community mobility, public services, and local socio-economic activities. However, limited community understanding of construction engineering often results in inadequate planning and implementation, reducing the quality and sustainability of road infrastructure. This community service program aimed to enhance community capacity in planning and implementing environmental road construction in RT 02 RW 04, Wangon Village. The program employed a participatory approach consisting of problem identification, field surveys, technical measurements, work volume calculations, preparation of the Bill of Quantities (BOQ) and Cost Estimate (RAB) based on the 2026 Standard Unit Price (SSH), technical assistance, and evaluation. The program resulted in technical planning documents, including work volume calculations and a cost estimate, while improving participants' understanding of construction planning, material selection, quality control, and road maintenance. Furthermore, the program strengthened community capacity in understanding technical construction documents, thereby supporting more effective, efficient, transparent, and sustainable environmental road development.